Ultrafast molecular imaging studies with laser-induced electron diffraction at high repetition rates - Hosseini Zavareh, Sajed (Kansas State University, 2024)
Laser induced electron diffraction (LIED) is a technique developed in the 1990s that leverages high-intensity ultrashort pulse lasers to capture femtosecond dynamics and provide detailed imaging capabilities of molecular and atomic structures. For decades, conventional gas phase electron diffraction (CED) has been the preferred method for determining inter-nuclear separations of isolated molecules at equilibrium, with modern implementations achieving spatial resolutions at the femtometer scale. However, the reliance on an electron gun in CED has limited its temporal resolution, making it difficult to capture atomic motion during chemical transformations. The electrostatic repulsion within the electron bunch, restrict the electron pulse duration to approximately 1 picosecond. Approximately thirty years after the invention of the first laser in 1960, the development of chirp pulse amplification (CPA) in the 1980s revolutionized atomic, molecular, and optical (AMO) physics by enabling sub-picosecond pulses with high intensities, facilitating the generation of ultrashort electron pulses. This advancement also opened new possibilities for dynamic molecular imaging through intense laser-matter interactions. In recent years, ultrafast electron diffraction (UED) has emerged using CPA technology to generate electron guns with temporal resolutions down to 100 fs. Along with UED, LIED was developed to overcome the limitations of CED, offering femtosecond temporal resolution. The foundation of the LIED was shaped after discovery of the three-step model in strong field physics (SFP) during the 1990s. When atoms and molecules are exposed to high intensity laser pulses, electrons are tunnel ionized. Post ionization, the liberated photoelectrons are accelerated and decelerated in the cycle of the laser field, and might recollide with the ion parent and could elastically rescatter. The latter defines the whole concept of LIED under the three step model. Until now, extensive studies has been done in LIED for atoms, diatomic molecules, small hydrocarbon molecules, and large molecules. Our ultimate goal in the Blaga group here at James R. McDonald laboratory (JRML) is to demonstrate pump-probe studies on molecules using the LIED technique. Although LIED has been a powerful tool for imaging molecules, recording a photoelectron angular distribution (PAD) currently takes several hours with 1 kHz lasers and standard time-of-flight (TOF) chambers. This process becomes even more time-consuming when PADs need to be collected at multiple time delays for pump-probe studies, taking up to a day for 10 different delays. In this dissertation, we accomplished two main objectives. First, we enhanced JRML’s LIED experimental capabilities by improving data collection rates by three orders of magnitude. We achieved this by developing a well-suited spectrometer for LIED, utilizing a high repetition rate laser, and implementing a fast data acquisition system. We constructed a specialized time-of-flight (TOF) setup for LIED experiments, featuring a one-meter double-sided TOF (D-TOF) equipped with two custom-built multi-anode multichannel detectors, with total of 10 anodes. This configuration reduces data collection time by an order of magnitude compared to standard single-anode TOFs. Additionally, the combination of the D-TOF (providing a tenfold reduction) and a Yb-based 100 kHz laser (providing a hundredfold reduction) decreases the data collection time by three orders of magnitude compared to standard single-anode TOFs integrated with 1 kHz laser sources. Coupled with a fast data acquisition system capable of handling the high data rates, the D-TOF setup has dramatically improved our experimental efficiency. Second, we studied subtle molecular differences by undertaking the first LIED study of butane isomers. This work highlights the potential of LIED to resolve structural differences with high precision, advancing our understanding of molecular structures. we provide theoretical and experimental evidence demonstrating the ability of LIED to effectively distinguish between n-butane and isobutane. Our findings also shows LIED’s potential for concurrently probing the nuclear and electronic structure of a molecule.
Keywords: Ultrafast molecular imaging; Laser-induced electron diffraction; Strong field physics; Time of flight; Atomic molecular optical physics